The Dual Role of NRF2 in Colorectal Cancer: Targeting NRF2 as a Potential Therapeutic Approach - Hu M; Yuan L; Zhu J (Dove Medical Press, 2024)
Mengyun Hu,1 Lingling Yuan,1 Jie Zhu2 1School of Clinical Medicine, Chengdu University of Traditional Chinese Medicine, Chengdu, People's Republic of China; 2Hospital of Chengdu University of Traditional Chinese Medicine, Oncology Department II, Chengdu, People's Republic of ChinaCorrespondence: Jie Zhu, Hospital of Chengdu University of Traditional Chinese Medicine, Oncology Department II, Chengdu, 37 Shierqiao Road, Jinniu District, Chengdu City, Sichuan Province, People's Republic of China, Tel +86 17781808796+86, Email cdzj001@sina.comAbstract: Colorectal cancer (CRC), as the third most common bisexual cancer worldwide, requires urgent research on its underlying mechanisms and intervention methods. NRF2 is an important transcription factor involved in the regulation of redox homeostasis, protein degradation, DNA repair, and other cancer processes, playing an important role in cancer. In recent years, the complex role of NRF2 in CRC has been continuously revealed: on the one hand, it exhibits a chemopreventive effect on cancer by protecting normal cells from oxidative stress, and on the other hand, it also exhibits a protective effect on malignant cells. Therefore, this article explores the dual role of NRF2 and its related signaling pathways in CRC, including their chemical protective properties and promoting effects in the occurrence, development, metastasis, and chemotherapy resistance of CRC. In addition, this article focuses on exploring the regulation of NRF2 in CRC ferroptosis, as well as NRF2 drug modulators (activators and inhibitors) targeting CRC, including natural products, compounds, and traditional Chinese medicine formulations.Keywords: NRF2, CRC, ferroptosis, pharmacological modulators